Edukasi Tentang Pijat Bayi Terhadap Ibu Untuk Meningkatkan Pertumbuhan Dan Perkembangan Bayi Di Klinik Citra Kota Medan - Adelina Fitri Tanjung; Adriana Bangun; Eka Ristin Tarigan; Achmad Zulfikar Siregar; Nadiyah Salsabila; Sylvira Rianda; Vidya Desriyani; Siti Aisyah Sa’adah (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
Baby massage is a beneficial form of stimulation that supports infant growth and development by increasing relaxation, blood circulation, and stimulating the nervous and digestive systems. However, many mothers still lack adequate knowledge and skills regarding proper infant massage techniques. This community service activity aims to improve mothers' knowledge and skills regarding infant massage as an effort to support infant growth and development. The activity was held at the Citra Clinic in Medan City, targeting mothers with babies aged 0–12 months. The methods used included health education, interactive discussions, demonstrations, and infant massage practice using a baby phantom. Evaluation was conducted through pre- and post-tests to measure participants' knowledge and skills during the activity. A total of 10 mothers participated in this activity. Participants were predominantly mothers aged 20–30 years (80%), had a high school education (70%), and were self-employed (70%). The evaluation results showed an increase in knowledge after the education. The lowest score increased from 53 to 80, the highest score from 73 to 93, and the average score from 63 to 87. Participants also demonstrated high enthusiasm during the discussion and practice sessions and were able to better practice infant massage techniques. These results indicate that education combined with demonstrations and hands-on practice effectively improves mothers' knowledge and skills in infant massage. This activity is expected to encourage mothers to independently practice infant massage at home as a form of stimulation to support optimal infant growth and development. Therefore, similar activities need to be implemented continuously as a promotive and preventive effort in healthcare facilities.